Remittance and Migration Prospects for the Twenty-First Century - Frédéric Docquier; Joël Machado (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
Remittances have been increasingly perceived as offering a vital lifeline for millions of poor households in developing countries. Their future will be affected by the evolution of emigration rates and cross-country disparities in income. In this paper, we provide integrated projections of income, population, migration stocks and remittances for the 21st century under alternative technological and policy scenarios. Our quantitative analysis reveals that remittances will be a sustainable source of funding for low-income countries. Due to rising income disparities and the take-off of emerging countries, their share in GDP is likely to increase in the future, notwithstanding the fact that population growth will be greater in low-income countries. The average remittances-to-GDP ratio will be constant in our worst-case scenario, multiplied by 3 in our baseline, and by 10 in our best-case scenario. The latter assumes that the BRIC's catch up with high-income countries and open their borders to immigration, and a constant propensity to remit.
Keywords: F22; F24; J11; J61; O15; 330